1. ## Derivatives Quotient Rule

In the problem f(x) = -1/x^2+1 finding the derivative using the quotient rule.

the solution would be -x^2+2x-1/(x^2+1)^2?

It seems right but im not sure.

2. Originally Posted by oregon88
In the problem f(x) = -1/x^2+1 finding the derivative using the quotient rule.

the solution would be -x^2+2x-1/(x^2+1)^2?

It seems right but im not sure.

$\displaystyle f'(x) = \frac{2x}{(x^2+1)^2}$

Wolfram gets the same answer I do. If you are unsure about how to use the quotient rule here the chain rule works equally well

Spoiler:
By the chain Rule:

$\displaystyle f(x) = -(x^2+1)^{-1}$

$\displaystyle f'(x) = (x^2+1)^{-2} \cdot 2x = \frac{2x}{(x^2+1)^2}$

3. $\displaystyle f(x)=-x/x^2+1$

$\displaystyle f'(x)=(x^2+1)d/dx(-x)-(-x)d/dx(x^2+1)/(x^2+1)^2$

$\displaystyle (x^2+1)(-1)-(-x)(2x)/(x^2+1)^2$

$\displaystyle -x^2+2x-1/(x^2+1)^2$

Is what I came up with

4. Originally Posted by oregon88
$\displaystyle f(x)=-x/x^2+1$

$\displaystyle f'(x)=(x^2+1)d/dx(-x)-(-x)d/dx(x^2+1)/(x^2+1)^2$

$\displaystyle (x^2+1)(-1)-(-x)(2x)/(x^2+1)^2$

$\displaystyle -x^2+2x-1/(x^2+1)^2$

Is what I came up with
Hold on, you said $\displaystyle f(x) = -\frac{1}{x^2+1}$ in the OP. Which one is correct?

Your differentiating is correct but your simplification on the third line is not - there should be no x term. Plus be more clear with your syntax using brackets

$\displaystyle u = -x \: \rightarrow \: u' = -1$

$\displaystyle v = x^2+1 \: \rightarrow \: v' = 2x$

$\displaystyle f'(x) = \frac{-x^2-1 + 2x^2}{(x^2+1)^2} = \frac{x^2-1}{(x^2+1)^2}$

5. The original problem is

$\displaystyle f(x) = \frac {-x}{x^2+1}$

Sorry about that, I see where I messed up on the third line I did not factor the (-x)(2x) on my paper. Thanks for the help e^(i*pi)